2008
DOI: 10.1002/pmic.200800066
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling in an animal model of acute pancreatitis

Abstract: Acute pancreatitis is an inflammatory disease of the pancreas, which evolves in approximately 20% of the patients to a severe illness associated with a high mortality rate. In this study, we performed a comparative proteomic analysis of pancreatic tissue extracts from rats with acute pancreatitis and healthy rodent controls in order to identify changes in protein expression related to the pathobiological processes of this disease. Pancreatic extracts from diseased and controls rats were analyzed by 2-DE and MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…In addition to native A1I3, strong bands corresponding to A1I3 fragments were detected. These fragments resulted from A1I3 anti-protease activity [5,7]. REG3A showed a different kinetics: no change was detected at 2 h post-induction, a moderate increase in protein expression was observed at 6 h, and a strong overexpression was visible at 18 h. In contrast, the concentration of cytochrome c in pancreatic extracts was shown to decrease progressively from T0 to T18h.…”
Section: 4mentioning
confidence: 85%
See 2 more Smart Citations
“…In addition to native A1I3, strong bands corresponding to A1I3 fragments were detected. These fragments resulted from A1I3 anti-protease activity [5,7]. REG3A showed a different kinetics: no change was detected at 2 h post-induction, a moderate increase in protein expression was observed at 6 h, and a strong overexpression was visible at 18 h. In contrast, the concentration of cytochrome c in pancreatic extracts was shown to decrease progressively from T0 to T18h.…”
Section: 4mentioning
confidence: 85%
“…Results from those studies showed that proteomic analysis, while being obviously not comprehensive, allowed obtaining a general picture of the main proteins pathways involved in AP pathobiology. Mass spectrometry (MS) analysis also provided for some proteins, such as protease inhibitor alpha-1-inhibitor 3, precise sequence information that could be correlated with specific pathobiological processes [5,6]. Finally, investigation of the protective effect of thermal stress suggested that proteins associated to the acinar cell secretory pathway play an important role in the modulation of AP severity [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Apoa1 is involved in inflammation and increased during pancreatitis in rats [23]; serpinA3k is reported to have a protective function in pancreatitis since it is a proteinase inhibitor and thus important to limit the activity of proteinases that are released prematurely in the pancreatic tissue [24]; and Prdx6 is associated with elevated oxidative stress [25,26]. None of these three proteins showed significant difference in protein levels between the two strains.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory eff ect of AM on proteinases suggests for it a protective role in the development of pancreatitis. The role of AM in the acute attack is undisputed and, once pancreatitis is established, its expression increases signifi cantly [ 20 ] . These fi ndings suggest a protective eff ect of MFP in the evolution of pancreatitis and that the increase of AM could be the limiting factor in the severity of acute pancreatitis.…”
mentioning
confidence: 99%